The renal nerves in chronic heart failure: efferent and afferent mechanisms - Schiller, Alicia M.; Pellegrino, Peter R.; Zucker, Irving H. (Frontiers in Physiology, 2015)
The function of the renal nerves has been an area of scientific and medical interest for many years. The recent advent of a minimally invasive catheter-based method of renal denervation has renewed excitement in understanding the afferent and efferent actions of the renal nerves in multiple diseases. While hypertension has been the focus of much this work, less attention has been given to the role of the renal nerves in the development of chronic heart failure (CHF). Recent studies from our laboratory and those of others implicate an essential role for the renal nerves in the development and progression of CHF. Using a rabbit tachycardia model of CHF and surgical unilateral renal denervation, we provide evidence for both renal efferent and afferent mechanisms in the pathogenesis of CHF. Renal denervation prevented the decrease in renal blood flow observed in CHF while also preventing increases in Angiotensin-II receptor protein in the microvasculature of the renal cortex. Renal denervation in CHF also reduced physiological markers of autonomic dysfunction including an improvement in arterial baroreflex function, heart rate variability, and decreased resting cardiac sympathetic tone. Taken together, the renal sympathetic nerves are necessary in the pathogenesis of CHF via both efferent and afferent